Stiffness of resting lumbar myofascia in healthy young subjects quantified using a handheld myotonometer and concurrently with surface electromyography monitoring. Issue 2 (April 2016) - Nair, Kalyani; Masi, Alfonse T.; Andonian, Brian J.; Barry, Alexander J.; Coates, Brandon A.; Dougherty, John; Schaefer, Emily; Henderson, Jacqueline; Kelly, Joseph
Summary: This study aimed to non-invasively quantify passive stiffness of superficial myofascia at a lower lumbar (L3-L4) anatomical level in young healthy male and female subjects and investigate its possible morphological variation. Resting prone lumbar myofascial measurements were quantified using MyotonPro ® and statistically analyzed in 20 young healthy individuals over 3-weekly intervals, concurrently with surface electromyography (sEMG). Averaged mean ± SE stiffness (Newton/meter) over three weeks was significantly (p < 0.001) greater in males (247.8 ± 11.3) than females (208.4 ± 11.3), on the right (237.7 ± 12.8) than left sides (218.5 ± 12.3), at 10-min (231.4 ± 9.1) than initial baseline (224.8 ± 9.1) values. A polymorphism of stiffness values in 10 male and 10 female subjects was suggested by box plot analyses of the 3 weekly measurements and greater inter-individual than intra-individual variances. Greater knowledge of lumbar myofascial stiffness can improve understanding of their contributions in health and chronic low back disorders.